Intrinsic growth and microzooplankton grazing on toxigenic Pseudo‐nitzschia spp. diatoms from the coastal northeast Pacific - M. Brady Olson; Evelyn J. Lessard; Lessard Cochlan; Vera L. Trainer (Limnology and Oceanography, 2008)
We investigated the population ecology of toxigenic diatoms within the genus Pseudo‐nitzschia on the Pacific Northwest coast during 2003, 2004, and 2005. Pseudo‐nitzschia spp. were widespread and abundant across the region, and the maximum density reached at our experimental stations was ~7 × 10 6 cells L ‐1 . Pseudo‐nitzschia spp. biomass did not correlate with total phytoplankton biomass, indicating that the growth response and/or mortality rate of Pseudo‐nitzschia spp. were dissimilar to other phytoplankton. In dilution experiments across wide‐ranging ocean conditions, Pseudo‐nitzschia spp. intrinsic growth rates were moderate to high (mean = 0.97 d −1 , range 0.24 d −1 to 2.30 d−1 , n = 36), and they were consistently higher than the corresponding growth rates of the aggregate 5‐mm chlorophyll a (Chl a ) communities. Pseudo‐nitzschia spp. growth was predicted by irradiance and temperature but not ambient nitrate concentration, whereas both Chl a size fractions showed dependence upon nitrate for growth. Microzooplankton grazing rates on Pseudo‐nitzschia spp. were moderate (mean = 0.32 d ‐1 , range 0.00 d ‐1 to 1.70 d ‐1 , n = 36); they were nearly always lower than corresponding Pseudo‐nitzschia spp. intrinsic growth, significantly lower than the grazing rates on the a size fraction, and comparable to grazing rates on the >5‐mm Chl a size fraction. Our results show that the strong competitive fitness of Pseudo‐nitzschia spp. results more from expression of characteristics that enable sustained high growth during variable and unfavorable conditions than from intrinsic adaptations that reduce grazing mortality.